2020
DOI: 10.1182/blood.2019002697
|View full text |Cite
|
Sign up to set email alerts
|

Impact of NPM1/FLT3-ITD genotypes defined by the 2017 European LeukemiaNet in patients with acute myeloid leukemia

Abstract: Patients with acute myeloid leukemia (AML) harboring FLT3 internal tandem duplications (ITDs) have poor outcomes, in particular AML with a high (≥0.5) mutant/wild-type allelic ratio (AR). The 2017 European LeukemiaNet (ELN) recommendations defined 4 distinct FLT3-ITD genotypes based on the ITD AR and the NPM1 mutational status. In this retrospective exploratory study, we investigated the prognostic and predictive impact of the NPM1/FLT3-ITD genotypes categorized according to the 2017 ELN risk groups in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 40 publications
6
109
0
Order By: Relevance
“…Thus, the results may not be generalizable to patients receiving therapy outside of evaluated clinical trials, low-intensity regimens (e.g., azacytidine), or targeted agents (e.g., midostaurin). Nonetheless, some recent biomarker studies suggest that previously recognized prognostic factors remain highly informative and predictive for responses to more “targeted’ agents [ 57 – 59 ], and as such, there likely remains some role for the identification of prognostic biomarkers that are applicable across a variety of therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the results may not be generalizable to patients receiving therapy outside of evaluated clinical trials, low-intensity regimens (e.g., azacytidine), or targeted agents (e.g., midostaurin). Nonetheless, some recent biomarker studies suggest that previously recognized prognostic factors remain highly informative and predictive for responses to more “targeted’ agents [ 57 – 59 ], and as such, there likely remains some role for the identification of prognostic biomarkers that are applicable across a variety of therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Regulome score 2b. 4 7 IL8_ IVS1 + 230 (+396) rs2227307 G Associated with IL8 at both transcriptional and translational levels and with increased transmigration of primary neutrophils. Associated with follicular lymphoma patient survival 6 , 7 CXC-Chemokine receptor 2 (IL8RB) CXCR2_Ex3-1010 rs1126580 G Associated with CXCR2 and CXCR1 levels in whole blood (GTEx).…”
Section: Material Subjects and Methodsmentioning
confidence: 99%
“…Even though cytogenetic analysis have allowed the stratification of AML patients into favourable, intermediate and unfavourable classes and has improved our ability to predict clonal evolution and disease progression 3 , many AML patients (~ 45%) have a normal karyotype, which suggests that additional genetic alterations are needed to develop the disease. Sequencing studies identified genes frequently mutated in AML, some of which predict poor prognosis ( NPM1 wt / FLT3-ITD high , RUNX1 , ASXL1 and TP53 ) 4 . Furthermore, it is increasingly evident that host immunity might also be implicated in AML risk and survival 5 .…”
Section: Introductionmentioning
confidence: 99%
“…in AML compared to other cancers, these mutations can be combined in complex ways in different subclones, making each patient almost unique in its genetic profile. Even taken into account the two most common mutations in AML; insertion in the NPM1 gene and internal tandem duplication (ITD) in the FLT3 gene, the combination of these two mutations with consideration of differing allele burdens can lead to different prognostic subgroup classifications with treatment-related consequences [12]. Furthermore, incorporating other currently targetable mutations, such as IDH1 and IDH2 mutations [10,11], the picture becomes even more complex.…”
Section: Making Treatment Approaches Fit Together For Individual Patimentioning
confidence: 99%